Clinical and pathological characterization of Central Nervous System cryptococcosis in an experimental mouse model of stereotaxic intracerebral infection. - Mohamed F Hamed; Vanessa Enriquez; Melissa E Munzen; Claudia L Charles-Niño; Mircea Radu Mihu; Habibeh Khoshbouei; Karina Alviña; Luis R Martinez (Public Library of Science (PLoS), 2023)
Infection of the Central Nervous System (CNS) by the encapsulated fungus Cryptococcus neoformans can lead to high mortality meningitis, most commonly in immunocompromised patients. While the mechanisms by which the fungus crosses the blood-brain barrier to initiate infection in the CNS are well recognized, there are still substantial unanswered questions about the disease progression once the fungus is established in the brain. C. neoformans is characterized by a glucuronoxylomannan (GXM)-rich polysaccharide capsule which has been implicated in immune evasion, but its role during the host CNS infection needs further elucidation. Therefore, the present study aims to examine these key questions about the mechanisms underlying cryptococcal meningitis progression and the impact of fungal GXM release by using an intracerebral rodent infection model via stereotaxic surgery. After developing brain infection, we analyzed distinct brain regions and found that while fungal load and brain weight were comparable one-week post-infection, there were region-specific histopathological (with and without brain parenchyma involvement) and disease manifestations. Moreover, we also observed a region-specific correlation between GXM accumulation and glial cell recruitment. Furthermore, mortality was associated with the presence of subarachnoid hemorrhaging and GXM deposition in the meningeal blood vessels and meninges in all regions infected. Our results show that using the present infection model can facilitate clinical and neuropathological observations during the progression of neurocryptococcosis. Importantly, this mouse model can be used to further investigate disease progression as it develops in humans.